Vegetative Growth Response of Entog Dwarf Coconut (Cocos Nucifera L.) to Different Planting Hole Size and Compound Inorganic Fertilizer Application - Natalina Zalukhu; Anita Costanci Christine Tengker; Yulianus Rompah Matana; Helen Joan Lawalata; Marthy Lingkan Stella Taulu (Institute for Research and Community Services Udayana University (LP2M Universitas Udayana), 2023)
Entog Dwarf coconut is a national superior variety. The purpose of this study was to determine the vegetative growth of Entog Dwarf coconut at 7-10 months of age. The research was conducted at the Palm Plant Research Institute in Manado (Upper Kima Experimental Garden and Ecophysiology Laboratory) using a factorial group randomized design with 2 factors and 3 replications. The first factor was the planting hole with a depth of 100cm and 60cm. The second factor was compound inorganic fertilizer with doses of 1.5kg, 1.0kg, 0.5kg, and control. Nutrient analysis of soil and leaves without fertilization at 7 and 10 months and after fertilization at 10 months. The results of the analysis of variance at the 5% level showed that planting holes had a significant effect, while compound inorganic fertilizers had a significant effect on vegetative characters. The tallest plants were about 51.2-63.7cm with a dose of 0.5-1.5kg while the shortest was 27.2cm, the largest stem circumference was 10.8-11.3cm with a dose of 0,5kg and 1.5kg while the smallest was 6.42cm, and the largest number of leaves was 3.67 midribs with a dose of 1.5kg while the smallest number was 2.67 midribs, where all vegetative characters were categorized as low in control plants. The interaction between the two factors had no significant effect on vegetative growth. The vegetative characters observed were positively correlated. The results of nutrient analysis of pH, moisture content, organic carbon, nitrogen, phosphorus, potassium, stomatal index, and chlorophyll showed little difference both without fertilization and after fertilization.